A single-center retrospective analysis of first-line therapy of multiple myeloma with bendamustine–bortezomib–dexamethasone. Issue 9 (1st September 2016) - Zwickl, Hannes; Zwickl-Traxler, Elisabeth; Pecherstorfer, Martin
Abstract: The aim of this retrospective study was to evaluate the efficacy and toxicity profile of bendamustine, bortezomib, and dexamethasone (BBD) combination treatment of patients with newly diagnosed multiple myeloma (MM). BBD treatment had a response rate of 80% regarding patients with ≥ partial response (PR). Median time to best response was 87.5 days and PFS was 22 months. Median of OS was not reached. PFS of non-responding patients was significantly shortened compared to those with ≥ PR. No statistically significant differences were determined concerning age (≥ vs. < 68 years) and ISS stage (ISS stage I/II vs. III). Grade 3 hematological effects and grade 3/4 non-hematological effects occurred in 20% and 35% of patients, respectively. Most pronounced hematological adverse event was leukopenia, the most severe non-hematological ones affected the cardiovascular system. In summary, BBD treatment was of acceptable efficacy in patients with newly diagnosed MM and exhibited rather low toxicity.